Development trends of some sectors of priority technologies in period to 2030 year - Hai, Nguyen Hoang; Tuan, Nguyen Quang; Hoa, Nguyen Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
Technologies pass development under strong impacts of the 4th Revolution of industrial development and a productivity revolution. The positions of science and technology (S&T) in the new context are reflected well in its guiding roles for socio-economic development thanks to impacts of fast changes and development to results and qualities of S&T activites. With the roles described in many studies as “platform”, “breakthrough”, “core” and “advancing”, technologies keep on guiding roles for development of modern manufacturing modes in service for targets of sustainable development, digitalization of manufacturing practice, enhancement of productivity, quality, effectiveness of development and competitiveness of national economy to 2030 and further. Vietnam is under preparation process of Strategies for science-technology-innovation (STI) for 2021-2030 period. The paper targets to give contributions to the preparation process of the Strategies. Code: 19061701 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">